Design of frequency selective surface based on Minkowski fractal and interdigital capacitance - Amir Khajevandi (Wiley, 2021)
Abstract In this paper, the Minkowski fractal is used to design the geometry of a frequency selective surface (FSS) unit cell, which resembles the shapes found in nature. The proposed FSS unit cell has both angular and polarization stabilities of incident wave. For the miniaturization of FSS and decrease of resonance frequency, interdigital capacitances (IDCs) are devised in the FSS structure, which do not eliminate angular and polarization stabilities. The dimensions of the unit cell are 5 mm × 5 mm and miniaturized 0.095λ0×0.095λ0. The resonance frequency is specified as 5.75 GHz with 155 MHz bandwidth. An equivalent circuit is derived for the unit cell to evaluate its frequency responses. The effects of variations of the geometrical dimensions of the FSS unit cell on its performance are studied. A prototype model of proposed FSS is fabricated and measured. The performance of its full‐wave computer simulation results and measured data are compared and are shown to be in good agreement.